PTH-021 Magnetic Anal Sphincter – a Novel Surgical Option for Management of Faecal Incontinence. (4th June 2013) - Tevlin, R; Hanly, A; Larkin, J; O'Connell, R
Abstract : Introduction: Faecal incontinence (FI) is a common and distressing problem with diverse aetiology and a significant economic burden 1, 2 . First-line therapy includes dietary modification, medication and biofeedback. Surgical options include sphincteroplasty, artificial bowel sphincter insertion, sacral nerve stimulation and stoma formation 3 . Recently, magnetic sphincter augmentation has been used successfully in gastro-oesophageal reflux disease 4 . A magnetic anal sphincter (MAS)(Torax Medical, Mn, USA) have been developed to reinforce an incompetent anal sphincter in FI. The MAS device consists of magnetic cores hermetically sealed within a series of titanium beads interlinked on independent titanium wires, forming a ring that rests around the external anal sphincter. The force required to separate the beads is approximately 100g, equivalent to normal defaecatory force 5 . Methods: Three multiparous females (47–54 years) with severe FI had MAS devices implanted under general anaesthesia. Two had failed neuromodulation, one had a failed sphincteroplasty and one incontinence after neo-chemoradiotherapy and colo-anal anastomosis for cancer. A curved, anterior perineal incision allowed creation of an extrasphincteric circumanal tunnel. Under fluoroscopic guidance and with fastidious antiseptic technique, the appropriate size MAS was inserted. All were discharged the same day. Results: Two patients with obstetric aetiologies reported significant improvement in continence at 6 weeks (St. Mark's Score 19 to 4 and 14 to 5 (24 = max worst score). The third patient, with anterior resection syndrome, developed a recalcitrant wound infection with subsequent device extrusion and explantation. Conclusion: MAS insertion is a novel, promising technique for management of FI. Further study is required prior to making definitive conclusions. Disclosure of Interest: None Declared. References: Mellgren A. Fecal Incontinence. Surgical Clinics of North America 2010; 90:185–194. Wald A. Fecal Incontinence in Adults. New England Journal of Medicine 2007; 356:1648–55. Lehur PA, Mc Nevin S, Buntzen S, Mellgren AF, Laurberg S, Madoff RD. Magnetic Anal Sphincter Augmentation for the Treatment of Fecal Incontinence: A Preliminary Report From a Feasibility Study. Diseases of the Colon and Rectum 2010; 53:1604–1610. Use of a magnetic sphincter for the treatment of GERD: a feasibility study. Gastrointestinal Endoscopy 2008; 67(2):287–294. Bharucha AE, Croak AJ, Gebhart JB, et al. Comparison of recto-anal axial forces in health and functional defecatory disorders. American Journal of Physiology – Gastrointestinal and Liver Physiology 2006; 290:1164–1169.